2019
DOI: 10.1108/ijoem-03-2019-0225
|View full text |Cite
|
Sign up to set email alerts
|

Time lag analysis of FDI spillover effect

Abstract: Purpose For the developing countries involving in the Belt and Road Initiative (BRI) with China as the main source of foreign development investment (FDI) and development as the top priority, it appears to attract more and more attention on how to make the best use of China’s outward foreign development investment. However, the contradictory evidence in the previous studies of FDI spillover effect and the remarkable time-lag feature of spillovers motivate us to analyze the mechanism of FDI spillover effect. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Cilt: 23 -Sayı: 44, Aralık 2020 Seren ÖZSOY BAUNSOBED, 23(44), 2020, 959-975 However, a fairly new study show that appropriate time lag of FDI spillover changes (see Zhang et al, 2019).…”
Section: Emprical Resultsmentioning
confidence: 99%
“…Cilt: 23 -Sayı: 44, Aralık 2020 Seren ÖZSOY BAUNSOBED, 23(44), 2020, 959-975 However, a fairly new study show that appropriate time lag of FDI spillover changes (see Zhang et al, 2019).…”
Section: Emprical Resultsmentioning
confidence: 99%
“…Sankaran et al [119], Rana and Sharma [120,121], and Wang and Ngene [122] suggested to overcome this problem by using the Wald or modified Wald (MWald) tests, but Hayashi et al [123] and Lemonte [124] demonstrated that, in small samples when used empirically to search for unimportant parameters, the Wald test procedure could be misleading. In furtherance of Zhang et al [125], Mao et al [126], Adebayo [97], and Chan et al [127], we used variance decomposition instead of the Wald test to explore the strengths of inter-variables causal interactions and to reveal potential causality impacts. The method was applied for nine consecutive periods from July 2020 till March 2021.…”
Section: Interactionmentioning
confidence: 99%
“…Increased Chinese FDI is associated with local industrial participation in the host countries. Zhang et al (2019) focus on the lag effect in the mechanism of FDI spillovers in developing countries and refer to systematic biases in this line of research. They point to studies like Demena and van Bergeijk (2017) whose review indicated negative or nonexistent spillover effects.…”
Section: Local Industry Participation In Africamentioning
confidence: 99%